Arkitektura a video documentary on the American colonial and contemporary traditions in Philippine architecture - Perez, Rodrigo D. (Tuklas sining series, 1994)
This documentary describes the public buildings and private structures built in the Philippines in the first half of the 20th century which served American colonial policies. It then moves on to present structures designed by Filipino architects after WWII who became concerned with the development of buildings that are congruent with Filipino history and culture, climatic and cultural conditions.